Architecture Of The Normative-Legal Information System, Methodological Provision Of Educational And Methodological Work Of The Institution Of Higher Education - Pichugin, М.Ф.; Sashchuk, I.M.; Pisarchuk, O.O.; Rakushev, М.Ю.; Kovbasyuk , C.B.; Gornin, M.A.; Fedorchuk, Д.Л. (Journal of Information Technologies in Education (ITE), 2009)
Purpose, functions, structure, electronic documents base contents and main issues of hardware and software architecture of the normative-legal information system, educational and methodological work of the institution of higher education are developed.